2021
DOI: 10.1101/2021.01.29.21250803
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Radiomics Analysis of Clinical Myocardial Perfusion Stress SPECT Images to Identify Coronary Artery Calcification

Abstract: PurposeMyocardial perfusion stress SPECT (MPSS) is an established diagnostic test for patients suspected with coronary artery disease (CAD). Meanwhile, coronary artery calcification (CAC) scoring obtained from diagnostic CT is a highly specific test, offering incremental diagnostic information in identifying patients with significant CAD yet normal MPSS scans. However, after decades of wide utilization of MPSS, CAC is not commonly reimbursed (e.g. by the CMS), nor widely deployed in community settings. We aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(78 reference statements)
0
3
0
1
Order By: Relevance
“…More recently we demonstrated that deep learning cardiac chamber volumes (from CTAC) provided incremental and complementary value to CAC and SPECT variables. 31 Ashrafinia et al used radiomic features from SPECT MPI to predict CAC score derived from CT scans 32 , whereas Amini et al applied a quantitative image analysis approach not only to diagnose CAD, but also for risk classification. 33 The proposed AI approach integrates simultaneous assessment of multiple structures on CTAC by leveraging strengths of deep learning and quantitative image analyses.…”
Section: Discussionmentioning
confidence: 99%
“…More recently we demonstrated that deep learning cardiac chamber volumes (from CTAC) provided incremental and complementary value to CAC and SPECT variables. 31 Ashrafinia et al used radiomic features from SPECT MPI to predict CAC score derived from CT scans 32 , whereas Amini et al applied a quantitative image analysis approach not only to diagnose CAD, but also for risk classification. 33 The proposed AI approach integrates simultaneous assessment of multiple structures on CTAC by leveraging strengths of deep learning and quantitative image analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been conducted in attempts to address this issue. Ashrafinia et al (28,29), applied texture and radiomics analysis to clinical myocardial perfusion SPECT imaging to predict coronary artery calcification (CAC) from CT imaging. A study by Kolossváry et al (30), showed that radiomics features are superior to conventional quantitative computed tomographic metrics in identifying coronary plaques with napkin-ring signs.…”
Section: Discussionmentioning
confidence: 99%
“…We subsequently provide discussions on our findings and a conclusion. This article was previously posted to the medRxiv preprint server on February 01, 2021 [ 31 ].…”
Section: Introductionmentioning
confidence: 99%